Studies of inclusive four-jet production with two b-tagged jets in proton-proton collisions at 7 TeV - Khachatryan, V. (2016)
Measurements are presented of the cross section for the production of at least four jets, of which at least two originate from b quarks, in proton-proton collisions. Data collected with the CMS detector at the LHC at a center-of-mass energy of 7 TeV are used, corresponding to an integrated luminosity of 3 pb(-1). The cross section is measured as a function of the jet transverse momentum for p(T) > 20 GeV, and of the jet pseudorapidity for |eta| < 2.4 (b jets), 4.7 (untagged jets). The correlations in azimuthal angle and pT between the jets are also studied. The inclusive cross section is measured to be sigma(pp -> 2b + 2j + X) = 69 +/- 3(stat) +/- 24(syst) nb. The eta and p(T) distributions of the four jets and the correlations between them are well reproduced by event generators that combine perturbative QCD calculations at next-to-leading-order accuracy with contributions from parton showers and multiparton interactions.